Effect of Acid-Base Property in Conjunction with Molecular Descriptors for Chemical Drugs and Bioactive Ingredients of Traditional Chinese Medicine on Prediction of Oral Absorption by Biopartioning Micellar Chromatography - Chen, Han; Liang, Yan; Juan Ren, Xiao; Mei Xiong, Dong; Rong Wang, Shu; Ping Wu, Li; Chen, Cong; Ming Ye, Li (Asian Journal of Chemistry, 2013)
This research was aimed to predict per cent of human oral absorption (HOA %) for drugs by biopartitioning micellar chromatography (BMC). A data set of 102 chemical drugs containing acidic, basic, neutral and amphiprotic drugs from various structure classes with oral absorption rate data available was studied to construct prediction models of oral absorption for all chemical drugs, acidic chemical drugs, basic chemical drugs and neutral chemical drugs respectively and proved the effect of the acid-base property of drugs on oral absorption. Oral absorption was reciprocally correlated to the negative value of the capacity factor (-1/k). The correlation was improved with the addition of molecular descriptors. According to established prediction models for chemical drugs, biopartitioning micellar chromatography was applied to predict oral absorption of the organic acids and alkaloids of traditional Chinese medicines (TCM) for bioactive ingredients basing on constructed quantitative structure-activity relationship/quantitative retention-activity relationship models of chemical drugs. The results showed that application was predictable and practical in bioactive ingredients of traditional Chinese medicines.